Background Activity Findings in End-Stage Renal Disease With and Without Comorbid Diabetes: An Electroencephalogram Study - Jatupornpoonsub, Tirapoot; Thimachai, Paramat; Supasyndh, Ouppatham; Wongsawat, Yodchanan (Frontiers in Human Neuroscience, 2021)
Renal failure and diabetes can induce cerebral complications, including encephalopathy, for which attentional and cognitive impairment are common symptoms. It is possible that renal failure with comorbid diabetes may induce more severe encephalopathy due to multiple pathogenic mechanisms. This concept was supported by the main findings of this study, which showed that EEG background activity between end-stage renal disease with and without comorbid diabetes was significantly different in relative power of delta in the eyes-open condition in frontoparietal regions, theta in the eyes-closed condition in all regions, beta in the parieto-occipital regions in both eye conditions, the delta/theta ratio in both eye conditions in frontoparietal regions, and the theta/beta ratio in all regions in the eyes-closed condition. These findings may increase awareness of comorbid cerebral complications in clinical practice. Moreover, the delta/theta ratio is recommended as an optimal feature to possibly determine the severity of encephalopathy.